Kerala Muslim history : a revisit - Bahāvuddīn, Ke. Eṃ (Other Books, 2012)
Kerala Muslim History: A Revisit, is part of an ongoing attempt by Prof. K.M. Bahauddin has contributed to shaping the public discourse in Kerala on many social issues. This work is the result of his extensive study about Kerala's Muslims.